jurnal Pengembangan Modul IPA Materi Sistem Tata Surya Berbasis Project Based Learning (PjBL) Untuk Meningkatkan Pengetahuan Faktual Dan Konseptual Siswa Kelas VI: Efektifitas Modul - GUSTAR AMAN, GUSTAR AMAN (UNIB Press, 2024)
This study aims to find out how to develop PjBL-based solar system science material modules and to determine the effectiveness of PjBL-based solar system science material modules in increasing students' factual and contextual knowledge. The research method used in this study is the ADDIE model consisting of five development stages which include the analysis stage, the design stage, the development stage, the implementation stage and the evaluation stage. The results showed that the PjBL-based solar system material science module was developed through an early stage analysis consisting of analysis of teacher needs and analysis of student needs and curriculum analysis. Then based on the results of the analysis phase, the module design is carried out. After that the module design is realized and validated by experts. Modules that have been validated by experts and declared feasible are then implemented to determine teacher and student responses to PjBL-based IPA modules. Lastly, an evaluation was carried out to determine the effectiveness of the Tata Suurya System Science material module in increasing students' factual and contextual knowledge. Based on the evaluation of the PjBL-based solar system material science module, it was found that the solar system site material science module is effective for increasing factual and conceptual knowledge based on the N gain score on increasing factual knowledge obtained by 0.75 with high classification and on increasing conceptual knowledge the score is Ngain obtained by 0.72 with high classification.